Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1530/eje-17-0468
|View full text |Cite
|
Sign up to set email alerts
|

Bone microarchitecture and estimated bone strength in men with active acromegaly

Abstract: Both cortical and trabecular microarchitecture are altered in men with acromegaly. Our data indicate that GH excess is associated with distinct effects in cortical vs trabecular bone compartments. Our observations also affirm the limitations of aBMD testing in the evaluation of patients with acromegaly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 29 publications
3
39
1
2
Order By: Relevance
“…Bone turnover is probably a better indicator of bone quality 101,102 (LQ), and proactive evaluations of vertebral fractures with the morphometric approach are recommended at diagnosis and annually thereafter 103 (SR). Assessment of bone microarchitecture in men with acromegaly has shown that alterations in both cortical and trabecular bone occur, which further corroborates the limitations of using areal BMD to assess fracture risk in these patients 104 . Soft tissue and bony craniofacial overgrowth result in considerable airway obstruction and respiratory complications in at least 25% of patients with acromegaly and might not be reversible despite the achievement of adequate biochemical control 49 (MQ).…”
Section: Complicationssupporting
confidence: 53%
“…Bone turnover is probably a better indicator of bone quality 101,102 (LQ), and proactive evaluations of vertebral fractures with the morphometric approach are recommended at diagnosis and annually thereafter 103 (SR). Assessment of bone microarchitecture in men with acromegaly has shown that alterations in both cortical and trabecular bone occur, which further corroborates the limitations of using areal BMD to assess fracture risk in these patients 104 . Soft tissue and bony craniofacial overgrowth result in considerable airway obstruction and respiratory complications in at least 25% of patients with acromegaly and might not be reversible despite the achievement of adequate biochemical control 49 (MQ).…”
Section: Complicationssupporting
confidence: 53%
“…us, it will take a relatively long term of treatment to assess aBMD changes in AGHD patients by DXA. High-resolution peripheral quantitative computerized tomography (HR-pQCT) provides details of bone microarchitecture and volumetric bone mineral density (vBMD) [12,13]. In our previous report, we found that young adults with childhood-onset growth hormone deficiency (CO AGHD) have prominently impaired vBMD and bone microarchitecture [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the effect of decreasing GH and IGF‐1 following treatment of cortical structures in acromegaly is less known; a reduction in cortical thickness could further compromise bone structural integrity. Indeed, mechanical and radiographic studies indicate that reduced cortical thickness increases the risk of hip fractures …”
Section: Introductionmentioning
confidence: 99%
“…(9,10) Thus, patients with newly diagnosed acromegaly have an increased risk of vertebral fractures, but low risk for peripheral fractures, (11) potentially because of increased CBT as assessed by pQCT. (12) The different mechanical demands to bone in a certain region determine the predominance of either trabecular or cortical bone. Vertebral bodies must resist high and repetitive axial compression loads and if the trabecular bone is reduced, the stress on the cortical compartments increases and the vertebral bone's ability to resist compression forces decreases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation